1980
DOI: 10.1111/j.1468-2958.1980.tb00134.x
|View full text |Cite
|
Sign up to set email alerts
|

Communication Apprehension and Achievement in a Performance-Oriented Basic Communication Course

Abstract: The study of communication apprehension (CA) impact in the instructional environment is extended through examination of all three CA levels relative to various performance situations in a basic communication course. Results indicate significant differences in achievement indices between all three CA groups on final course grade and the first two of four performance assignments. Moderate and high CA groups were not significantly different from each other on the third and fourth performance tasks. Low and high C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Those students who are skilled in articulating ideas may receive higher grades in part because of that ability. Both of these findings are consistent with results of studies that have examined the relationship between communication apprehension and academic success variables (McCroskey & Andersen, 1976;McCroskey et al, 1989;Powers & Smythe, 1980). If one were to create a causal model with SAT scores, GPA, and communication competence, it would be reasonable to argue that whereas communication competence influences GPA, that SAT scores (which are supposed to predict college GPA) might predict communication competence.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Those students who are skilled in articulating ideas may receive higher grades in part because of that ability. Both of these findings are consistent with results of studies that have examined the relationship between communication apprehension and academic success variables (McCroskey & Andersen, 1976;McCroskey et al, 1989;Powers & Smythe, 1980). If one were to create a causal model with SAT scores, GPA, and communication competence, it would be reasonable to argue that whereas communication competence influences GPA, that SAT scores (which are supposed to predict college GPA) might predict communication competence.…”
Section: Discussionsupporting
confidence: 78%
“…Without a satisfying roommate relationship, students may experience loneliness and may try to alleviate that loneliness by leaving college. Poor communication skills may also be associated with poorer academic performance, as some studies of communication apprehension have shown (McCroskey & Andersen, 1976;McCroskey et al, 1989;Powers & Smythe, 1980). The present study encompassed both the role of communication skills in the roommate relationship and in academic success.…”
mentioning
confidence: 93%
“…We can cite a body of research that tested the relationship between CA and academic achievement (Powers & Smythe, 1980), instructional preference (McCroskey & Anderson, 1976), and a variety of personality characteristics (McCroskey, Daly, and Sorensen, 1976;Lustig, 1974). (Consult McCroskey, 1977 for a full review.)…”
Section: The Context-ca and State-ca Relationshipmentioning
confidence: 99%
“…In performance-oriented classes, regardless of type (e.g., discussion, interpersonal, public speaking), students with high CA are consistently evaluated lower (Powers & Smythe, 1980;O'Mara et al, 1996). Furthermore, research into the mediation effects of other variables has served to increase the generalizability of a relationship between CA and academic achievement.…”
Section: Learning Pa Rticularly That Which Takes Place In the Traditmentioning
confidence: 99%